Proteostatic Regulation of MEP and Shikimate Pathways by Redox-Activated Photosynthesis Signaling in Plants Exposed to Small Fungal Volatiles - Ameztoy, Kinia; Sánchez-López, Ángela María; Muñoz, Francisco José; Bahaji, Abdellatif; Almagro, Goizeder; Baroja-Fernández, Edurne; Gámez-Arcas, Samuel; De Diego, Nuria; Doležal, Karel; Novák, Ondřej; Pěnčík, Ales; Alpízar, Adán; et al. (Frontiers in plant science, 2021)
Microorganisms produce volatile compounds (VCs) with molecular masses of less than 300 Da that promote plant growth and photosynthesis. Recently, we have shown that small VCs of less than 45 Da other than CO2 are major determinants of plant responses to fungal volatile emissions. However, the regulatory mechanisms involved in the plants' responses to small microbial VCs remain unclear. In Arabidopsis thaliana plants exposed to small fungal VCs, growth promotion is accompanied by reduction of the thiol redox of Calvin-Benson cycle (CBC) enzymes and changes in the levels of shikimate and 2-C-methyl-D-erythritol 4-phosphate (MEP) pathway-related compounds. We hypothesized that plants' responses to small microbial VCs involve post-translational modulation of enzymes of the MEP and shikimate pathways via mechanisms involving redox-activated photosynthesis signaling. To test this hypothesis, we compared the responses of wild-type (WT) plants and a cfbp1 mutant defective in a redox-regulated isoform of the CBC enzyme fructose-1,6-bisphosphatase to small VCs emitted by the fungal phytopathogen Alternaria alternata. Fungal VC-promoted growth and photosynthesis, as well as metabolic and proteomic changes, were substantially weaker in cfbp1 plants than in WT plants. In WT plants, but not in cfbp1 plants, small fungal VCs reduced the levels of both transcripts and proteins of the stromal Clp protease system and enhanced those of plastidial chaperonins and co-chaperonins. Consistently, small fungal VCs promoted the accumulation of putative Clp protease clients including MEP and shikimate pathway enzymes. clpr1-2 and clpc1 mutants with disrupted plastidial protein homeostasis responded weakly to small fungal VCs, strongly indicating that plant responses to microbial volatile emissions require a finely regulated plastidial protein quality control system. Our findings provide strong evidence that plant responses to fungal VCs involve chloroplast-to-nucleus retrograde signaling of redox-activated photosynthesis leading to proteostatic regulation of the MEP and shikimate pathways.
Keywords: proteostatic regulation; plant–microbe interaction; PQC system; MEP pathway; redox regulation: Clp protease system; chloroplast-to-nucleus retrograde signaling